Answer:
See solutions below
Step-by-step explanation
We are to find the equation of circle A and B
The equation of a circle is expressed as;
(x-a)^2 + (y-b)^2 = r^2
(a, b) is the centre and r is the radius
For Circle A that has center of (6, 7), and a radius of 4
Substitute;
(x-6)^2 + (y-7)^2 = 4^2
(x-6)^2+(y-7)^2 = 16
Hence the equation of circle A is (x-6)^2+(y-7)^2 = 16
For circle B:
If circle B has a center of (2, 4), and a radius of 16
The equation is expressed as;
(x-2)^2+(x-4)^2 = 16^2
(x-2)^2+(x-4)^2 = 256
Hence the required equation is (x-2)^2+(x-4)^2 = 256